Colchicine and quality of life in patients with acute coronary syndromes: results from the COPS randomized trial. (14th October 2021) - Dawson, L; Quinn, S; Tong, D; Boyle, A; Hamilton-Craig, C; Adams, H; Layland, J
Abstract: Background: Recent data suggest that colchicine may reduce cardiovascular events among patients presenting with acute coronary syndromes. This sub-study of the Australian COPS trial aimed to assess whether colchicine affects health status outcomes. Methods: Health status was assessed at baseline and 12-months using the EuroQol-5 Dimension 5-level (EQ-5D-5L) score and the full 19-question Seattle Angina Questionnaire (SAQ). Data were available for 786 patients (388 randomized to colchicine, 398 to placebo). Results: Baseline characteristics were well matched between groups; mean age was 60.1 (SD 14.8) years, and 20% were female. Baseline health status scores were impaired, and most parameters demonstrated significant improvement from baseline to 12-months (EQ-5D-5L Visual Analogue Score [VAS] 69.3 to 77.7; SAQ angina frequency score 83.0 to 95.3, both p<0.001). No significant differences in adjusted mean score change among any of the EQ-5D-5L or SAQ dimensions were observed between treatment groups in either intention-to-treat or per-protocol analysis. There were borderline interactions in EQ-5D-5L scores for those with previous MI vs not, and in SAQ scores for those with obesity vs not. In categorical analysis using observed data, patients treated with colchicine were more likely to have clinically significant improvement in physical limitation score over the period (36% improved vs. 28%, P<0.05). Baseline health status scores were not associated with the primary endpoint at 12 months. Conclusions: Treatment with colchicine did not appear to affect change in measures of health status following acute coronary syndromes, but it did lead to a greater likelihood of improvement in physical limitation scores. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Peninsula Health, Monash University